2016
DOI: 10.1016/j.vaccine.2016.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of protective B-cell epitopes of Atroxlysin-I: A metalloproteinase from Bothrops atrox snake venom

Abstract: Atroxlysin-I (Atr-I) is a hemorrhagic snake venom metalloproteinase (SVMP) from Bothrops atrox venom, the snake responsible for the majority of bites in the north region of South America. SVMPs like Atr-I produce toxic effects in victims including hemorrhage, inflammation, necrosis and blood coagulation deficiency. Mapping of B-cell epitopes in SVMPs might result in the identification of non-toxic molecules capable of inducing neutralizing antibodies and improving the anti-venom therapy. Here, using the SPOT-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Furthermore, the second 12-mer peptide corresponded to a non-significant peak centered around 15-mer number 69 in the signal profile for P22796. A similar study on a P-I SVMP from Bothrops atrox (P85420) determined segments 2 and 3 to be sufficient in raising a protecting antibody response against the toxin when rabbits were immunized with the corresponding synthetic peptides [31]. In both studies only immunization with combinations of peptides were reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the second 12-mer peptide corresponded to a non-significant peak centered around 15-mer number 69 in the signal profile for P22796. A similar study on a P-I SVMP from Bothrops atrox (P85420) determined segments 2 and 3 to be sufficient in raising a protecting antibody response against the toxin when rabbits were immunized with the corresponding synthetic peptides [31]. In both studies only immunization with combinations of peptides were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the inability to evaluate discontinuous epitopes, a growing number of studies have proven the usefulness of linear epitope analyses in antivenom research. Linear elements of epitopes have been found and the ability of synthetic mimicking peptides to induce a neutralizing antibody response have been demonstrated, opening new possibilities to improve the efficacy of snakebite antivenoms in the near future [2531]. Due to technological limitations of traditional peptide synthesis and cellulose-bound peptide arrays (spot-synthesis) and the high number of overlapping peptides needed to perform such meticulous experiments, reported studies have each focused on no more than five toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Further, venomics will benefit from the rapidly increasing availability of genomic and transcriptomic data, to evolve its resolution power from a protein-family level, to a locus-resolution level, even encompassing proteoform variability [94]. Regarding antivenomics, the future should bring further refinements and application of techniques for determining the fine specificity of antibodies that recognize and neutralize toxins, identifying their most relevant antigenic determinants through strategies such as epitope mapping using sets of overlapping synthetic peptides [9597], including the recently reported use of high-density peptide microarray technology for such purpose [98]. Toxicovenomics, still in its infancy, will need to cope with limitations and challenges already discussed, on the resolution of native chromatography strategies, and the development of pertinent bioassays, preferably in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies involving immunoassay quantification of antivenom binding to immobilised synthetic peptides (SPOT synthesis), corresponding to individual segments of the amino acid sequence of a given toxin, have added valuable molecular insight by elucidating which sequences contain linear elements of epitopes recognised by given antivenoms67121314. These kind of meticulous epitope mapping experiments have also been performed on toxins from Tityus scorpions151617 and Loxosceles spiders18.…”
mentioning
confidence: 99%